2023
DOI: 10.3390/diagnostics13061108
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Muscle Weakness Due to Myasthenia Gravis Using Shear Wave Elastography

Abstract: Myasthenia gravis (MG) is often accompanied with muscle weakness; however, little is known about mechanical adaptions of the affected muscles. As the latter can be assessed using ultrasound shear wave elastography (SWE), this study characterizes the biceps brachii muscle of 11 patients with MG and compares them with that of 14 healthy volunteers. Simultaneous SWE, elbow torque and surface electromyography measurements were performed during rest, maximal voluntary contraction (MVC) and submaximal isometric cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In recent years, it has been shown that imaging technologies can play a major role in the diagnosis of myopathies [ 17 , 52 , 53 , 54 , 55 ]. B-mode ultrasonography can be used to evaluate muscle atrophy and decreased muscle size [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been shown that imaging technologies can play a major role in the diagnosis of myopathies [ 17 , 52 , 53 , 54 , 55 ]. B-mode ultrasonography can be used to evaluate muscle atrophy and decreased muscle size [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo characterization of skeletal muscles is crucial for understanding musculoskeletal diseases and improving treatment strategies. For this, the non-invasive ultrasound shear wave elastography (SWE) has recently been shown to represent both passive [1] , [2] , [3] , [4] and active muscle mechanics [5] , [6] , [7] , [8] in healthy cohorts and several studies have demonstrated the clinical potential for SWE, for example for patients diagnosed with myotonia [9] , Duchenne muscular dystrophy [10] , myasthenia gravis [11] or Parkinson [12] . However, applying SWE on skeletal muscles poses challenges due to the muscles' complex and heterogeneous architecture.…”
Section: Introductionmentioning
confidence: 99%